Stochastics and special education teaching: centered and uniform distributions - López-Mojica, José Marcos (2019)
This article is part of a more extensive project aimed at analyzing stochastics teaching and learning processes in special education. The teaching of this educational level is presented here using a qualitative approach. From a theoretical perspective, three guiding axes were considered: the epistemological, cognitive and social axes. The larger study was divided into three phases.  This paper will be focused partly on the second phase, particularly on the introduction of the probability distribution for four teachers in a guided study scenario, using teaching scripts and logbooks as instruments.  Data was recorded in video and in writing. In addition, operational body and teaching analysis unit were applied. Results include the teachers’ gradual acquisition of the ideas of sample space, probability measure, random variable (relative frequencies), distribution, and symmetry.